PENGARUH KONSENTRASI EKSTRAK BUAH MAHKOTA DEWA (Phaleria macrocarpa (Scheff.) Boerl) TERHADAP ADHESI BAKTERI Streptococcus mitis (Kajian In Vitro) - , SABDAYANA; , drg. H. Dedy Kusuma Yulianto, M.Biotech ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Pathogenecity of caries was started by plaque formation. Plaque was one of biofilm masses that could be attached to tooth surface. Plaque formation was started by adhesion of pioneer bacteria, that is Streptococcus mitis (S. mitis). The aim of this study was to determine the effectPhaleria macrocarpa (Scheff.) Boerl extract against S. mitis adhesion. Phaleria macrocarpa (Scheff.) Boerl extract in this study were obtained by maceration procedure with etanol 96% as the solvent. Then the extract was filtered by 0,22Î¼m milipore and diluted with aquadest to get 25%, 27,5% and 30% concentrations. S. mitis used in this study was isolated from pure cultures from Balai Laboratorium Kesehatan Yogyakarta. There were three treatment groups in this study: extract groups (25%, 27,5%, and 30%), the positive control group (chlorhexidine gluconate 0,12%) and the negative control grup (aquadest). The results were tested by spectrophotometer 600 nm. The optical density (OD) was then incorporated in a formula to get percentage of bacterial adherence for each sample. One way ANOVA test showed that there were effect of the Phaleria macrocarpa (Scheff.) Boerl extracton S. mitis adhesion. S. mitisadhesion were getting lower as increased of the concentration extract.Percentageadhesiongroupconcentration30% were lower thanthe positivecontrolandbased onLSDtest they both hadsignificant differences. The conclusion in this study was the extract with 30% concentration had better ability with clorhexidine gluconate to inhibit S. mitis adhesion.